Grants of the MATRA program for public and educational organizations in conditions of war (Economics and region, 2024)
The article examines the possibilities of grant assistance under the Matra Program implemented by the Kingdom of the Netherlands in Ukraine. The analysis of the support of the Matra Program showed that for Ukraine it actualized a grant competition with the possibility of attracting 300,000 - 500,000 euros per project. It is emphasized that the Matra Program in this competition is aimed at public and educational organizations that wish to implement projects to meet the needs of the Ukrainian people during the war, overcome the consequences of Russian aggression, continue the reform process, prepare for post-war recovery and reconstruction and European integration of Ukraine. It is noted that the Program focuses on non-profit organizations that are officially registered in Ukraine. However, international organizations are also allowed to participate in the competition. It was emphasized that the grant instruments of the MATRA Program are an essential mechanism of assistance to Ukrainian society in wartime for the implementation of initiatives to preserve and restore the country in wartime and postwar periods. The focal topics of the Program are: strengthening of social unity and inclusiveness, i.e. participation of youth at the local level in war-affected communities; support of vulnerable categories, i.e. reintegration of internally displaced persons and war veterans; strengthening the rule of law with an emphasis on an independent judiciary, integrity, transparency and accountability; promotion of proper management and fight against corruption, in particular in the regions; providing support to recovery/reconstruction efforts of Ukraine, including transparent recovery; promoting parliamentary democracy, supporting democratic participation and mobilizing citizens: providing support to EU integration efforts, including reform advocacy. Recommendations have been developed for applicant organizations, the consideration of which will contribute to obtaining grant funding. Summarized, as a result of the implementation of the projects financed by the Matra Program, a significant impact of the activities of the grant recipients on various areas is expected for the preservation and restoration of Ukraine in the conditions of the war and the post-war period.
Keywords: grants; Matra program; assistance from the Netherlands; financing of public organizations; grants for educational organizations; grants for non-profit organizations; program opportunities; program requirements